2015
DOI: 10.1098/rsbl.2015.0058
|View full text |Cite
|
Sign up to set email alerts
|

Salivary oxytocin increases concurrently with testosterone and time away from home among returning Tsimane’ hunters

Abstract: Oxytocin, testosterone and cortisol can have opposing effects on social behaviour, yet few studies have examined their interactions. We measured changes in salivary oxytocin, testosterone and cortisol among Tsimane' men returning home after hunting, an ancient context of male status competition, parental investment and cooperation. Contra normal diurnal rhythm, oxytocin increased relative to baseline and this increase was positively associated with duration of the hunt and change in testosterone, but not corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Hence, these results also suggest that the interaction between testosterone and oxytocin is sexually dimorphic. Another study, which investigated hormonal shifts in Tsimané hunters, found that both, endogenous oxytocin and endogenous testosterone, increased after hunting [22]. The authors presumed that the elevated testosterone levels might have resulted from successful hunting while the increase of oxytocin could enhance social salience.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, these results also suggest that the interaction between testosterone and oxytocin is sexually dimorphic. Another study, which investigated hormonal shifts in Tsimané hunters, found that both, endogenous oxytocin and endogenous testosterone, increased after hunting [22]. The authors presumed that the elevated testosterone levels might have resulted from successful hunting while the increase of oxytocin could enhance social salience.…”
Section: Introductionmentioning
confidence: 99%
“…The authors presumed that the elevated testosterone levels might have resulted from successful hunting while the increase of oxytocin could enhance social salience. Further suggesting an interaction between both hormones was the fact that the percentage of increase of both hormones was strongly correlated [22]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OT can also augment Leydig cell testosterone production [127,128]. Studies in humans show that both testosterone and OT increase simultaneously in a range of activities from sexual activity [18], to hunting [46], to in-group/out-group competition [26,33], and that exogenous OT administration increased salivary testosterone levels and enjoyment from parenting in fathers [47] (though note that not all OT administration studies find concurrent increases in testosterone [129]). Taken at face value, this evidence may suggest the potential for OT and testosterone to work in concert to promote cooperative or coalitional behaviours.…”
Section: Synthesis and Future Directionsmentioning
confidence: 99%
“…The human feeding niche requires extensive bi-parental care, as well as additional multi-generational support, all of which would benefit from extensive tolerance by human males of both their offspring and other family members [45]. The anxiolytic and bonding aspects of increased OT may be a critical proximate mechanism that keeps human males engaged in familial provisioning [46].…”
Section: (B) Oxytocin and Male Parental Investmentmentioning
confidence: 99%